2021
DOI: 10.4103/jfmpc.jfmpc_2161_20
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of children with coronavirus at a joint commission-accredited hospital in the United Arab Emirates

Abstract: Objectives: Our aim was to identify the epidemiological characteristics and transmission patterns of coronavirus (COVID-19) among pediatric patients in the multicultural and multiethnic city of Al Ain in the United Arab Emirates (UAE). Method: A retrospective study was conducted by abstracting data from the electronic medical records of pediatric patients with COVID-19 from two major public hospitals in Al Ain. The data of patients from birth through 16 years of the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
(26 reference statements)
1
9
1
Order By: Relevance
“…The frequency of pediatric COVID-19 increased to 19.0% as of 7 April 2022 in the US [ 45 ]. Moreover, this study found a higher prevalence of COVID-19 among female pediatric patients than males (38% (95% CI: 24–53%)), contrary to other studies which reported male dominance, such as Al Mansoori et al (50.3%) [ 46 ], Dong Y et al (56.6%) [ 47 ], and Armin S et al(59.4%) [ 48 ]. The mean age of our population was 9.83 years while other studies reported a mean of 5.3 years [ 48 ].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The frequency of pediatric COVID-19 increased to 19.0% as of 7 April 2022 in the US [ 45 ]. Moreover, this study found a higher prevalence of COVID-19 among female pediatric patients than males (38% (95% CI: 24–53%)), contrary to other studies which reported male dominance, such as Al Mansoori et al (50.3%) [ 46 ], Dong Y et al (56.6%) [ 47 ], and Armin S et al(59.4%) [ 48 ]. The mean age of our population was 9.83 years while other studies reported a mean of 5.3 years [ 48 ].…”
Section: Discussioncontrasting
confidence: 90%
“…Such variations may emanate from differences in study population and location. However, our population had a median age of 7 years, with a range from birth to 16 years, which was similar to previous studies [ 46 , 47 ], indicating that children of all ages may be susceptible to COVID-19.…”
Section: Discussionsupporting
confidence: 88%
“…Among these, two articles were preprint versions [64,89]. There were 57 cohort [4][5][6][7][8][9][10][11][12]17,31,32,[34][35][36][37]39,41,42,44,49,53,58,66,69,71,73,[78][79][80][81][82][83][84]89,90,95,98,99,102,105,108,109,115,116,118,119,123,125,127,…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Only four studies were conducted within multiple countries (n = 4) [53,109,118,127]. The majority of the studies were single-center [4,6,[11][12][13][14][15][16]18,19,[21][22][23][32][33][34][35][38][39][40][41][43][44][45][46][48][49][50][51][52][55][56][57][59][60][61][62][64][65][66][67][68][69][70][72][73][74][75]…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…This is one of the retrospective studies in SA on the clinical features of pediatric patients with COVID-19. Studies published in late 2020 and 2021 were conducted in the SA and Gulf regions ( 5 , 15 , 22 24 ). However, three previous retrospective studies were published early in 2021: one retrospective study included 62 children from a single center in Jeddah, SA ( 25 ), the other conducted in a tertiary hospital in Riyadh included 742 pediatric inpatients and outpatients ( 6 ), and the last one conducted in three tertiary academic hospitals in SA enrolled 88 hospitalized children, the majority of whom had mild to moderate diseases ( 7 ).…”
Section: Discussionmentioning
confidence: 99%